2008
DOI: 10.1074/jbc.m708067200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human T Cell Receptor γδ-recognized Epitopes/Proteins via CDR3δ Peptide-based Immunobiochemical Strategy

Abstract: Human T lymphocytes, bearing T cell receptor (TCR) ␥␦, play an important role in anti-tumor/microbe immune responses. However, few tumor antigens recognized by TCR␥␦ have been defined so far. To investigate antigenic epitopes/proteins recognized by ␥␦T cells, we have established a new immunobiochemical strategy that uses complementarity-determining region 3 of TCR ␦ chain (CDR3␦) peptide-mediated epitope/protein-binding assays. CDR3␦ peptides synthesized using the CDR3 region in TCR V␦2 chain were validated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 34 publications
4
60
0
Order By: Relevance
“…With this novel strategy, we have successfully identified seven tumor-related epitopes, two hepatitis B virus (HBV) infection-related antigenic epitopes, and two self proteins including heat shock protein (HSP) 60 and human mutS homolog 2 (hMSH2) that are recognized by human ␥␦ TCR (7). These results further support that the primary sequence of CDR3␦ in ␥␦ TCR determine the specificity of antigen binding.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…With this novel strategy, we have successfully identified seven tumor-related epitopes, two hepatitis B virus (HBV) infection-related antigenic epitopes, and two self proteins including heat shock protein (HSP) 60 and human mutS homolog 2 (hMSH2) that are recognized by human ␥␦ TCR (7). These results further support that the primary sequence of CDR3␦ in ␥␦ TCR determine the specificity of antigen binding.…”
supporting
confidence: 59%
“…Nine peptides as putative epitopes were identified, among which seven were tumor-related and two were HBV infection-related. BLAST searches revealed that most matched proteins were conserved proteins of prokaryotes (7). Results suggest the possibility that ␥␦ TCR recognizes some conserved molecules.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…76 More recently, another putative Vc9Vd2 T cell tumor antigen, human MutS homologue 2 (MSH2), was identified using a peptide-based affinity screening system for the CDR3 of the d chain. 77 MSH2 is normally located in the nucleus where it functions as a DNA mismatch repair gene, but it is often mutated in a number of different types of epithelial cancers and can be ectopically expressed. 78 Transformation of normal human B cells by Epstein-Barr virus or subjecting renal carcinoma cell lines to oxidative stress also led to an increased surface expression of MSH2 and rendered them susceptible to Vc9Vd2 T cell-mediated cell lysis that could be blocked by the use of anti-MSH2 antibodies or downregulation of its gene expression.…”
Section: Vd2 T Cells: To Know the Complex Burden Of Being Humanmentioning
confidence: 99%
“…We found that synthesized OEC-derived CDR3d-peptides could mimic the TCRcd and bind specifically to tumor cell lines and tissues 25 A CDR3d-grafted antibody also showed specific binding to several tumor cells 19 We used synthesized OEC-derived CDR3d peptides as probes to search for putative TCR-binding epitopes by screening a 12-mer random peptide phage-displayed library and identified several putative TCR ligands within tumor cell extracts by affinity chromatography and liquid chromatography/electrospray ionization tandem mass spectrometry analysis. Nine peptides and two proteins that bound the cdTCR been identified including human mutS homolog 2, a novel cdTCR ligand 15,31 Another research group also found that the CDR3d region was responsible for the T22 protein binding specificity of the Vd2 T cells clone G8 32 We had previously constructed full-length PBMCs-derived c9 and d2 chains using overlapping PCR. The fulllength c9 and d2 chains with tumor antigen-specific CDR3 regions were stably transfected into J.RT3-T3.5 by electroporation and expressed functional c9d2TCR 26 In this study, we induced c9 and d2 (OT3) expression in PBLs using a retroviral vector and generated efficient tumor reactive T cells.…”
Section: Discussionmentioning
confidence: 99%